Emotional Resonance of 'Perfect': A Psycholinguistic Study of Listener Responses to Word Choice and Sentence Structure in Ed Sheeran's Lyrics - Zahra Mawaddah; Otong Setiawan Djauhari (INDO PUBLISHING, 2025)
This study aims to investigate how emotions emerge from word choice and sentence structure in the song Perfect by Ed Sheeran using a psycholinguistic approach. The song is widely recognized for evoking feelings of nostalgia, love, and happiness in its listeners. Employing a qualitative method through analytical observation, this research demonstrates how linguistic elements such as diction, repetition, and simple sentence construction contribute to the creation of emotional meaning. The findings indicate that the lyrics of Perfect prompt listeners to recall their own feelings through the use of clear language, recurring themes, and straightforward sentence structures, all of which enhance emotional closeness and resonance.